Oil palm empty fruit bunch extract as green corrosion inhibitor for mild steel in hydrochloric acid solution: Central composite design optimization. Issue 6 (2nd January 2019) - Haris, Nur Izzah Nabilah; Sobri, Shafreeza; Kassim, Norazila
Abstract : Oil palm empty fruit bunch (OPEFB) extract was evaluated as corrosion inhibitor for mild steel corrosion in 1 M hydrochloric acid using weight loss technique. OPEFB extract was prepared at various concentrations of 0.2–1.0 v/v% for preliminary study. Central composite design (CCD)‐based optimization was engaged to analyze the factors and to maximize inhibition efficiency. The highest inhibition efficiency was estimated up to 99.95%. Fourier transform infrared (FTIR) and scanning electron microscopy (SEM) studies confirmed the presence of active compounds and deposition of extract on metal surface. Thermodynamic study revealed that the adsorption obeyed Langmuir isotherm and inhibition mechanism inclined toward physisorption. Abstract : Oil palm empty fruit bunch (OPEFB) extract was evaluated as corrosion inhibitor for mild steel corrosion in 1 M hydrochloric acid using weight loss technique. Central composite design (CCD)‐based optimization was engaged to analyze the factors and to maximize inhibition efficiency. The highest inhibition efficiency was estimated up to 99.95%.